Adaptation and validation of the Digital Health Literacy Instrument for Portuguese university students. (17th February 2022) - Martins, Silvana; Augusto, Cláudia; Martins, Maria R. O.; José Silva, Maria; Okan, Orkan; Dadaczynski, Kevin; Duarte, Ana; Fronteira, Inês; Ramos, Neida; Rosário, Rafaela
Abstract: Background: Health literacy is an important skill to deal with information and positively influences individual and community health. Information concerning health is available from a plethora of online resources. The concept of digital health literacy has gained prominence with the pandemic. The absence of valid tools to analyse digital literacy levels are scant. This study aims to translate, adapt and validate the Portuguese version of the Digital Health Literacy Instrument (DHLI) as used in the global COVID‐HL Network. Methods: Participants were mostly students from social sciences, psychology, education and health sciences. The Portuguese version of the DHLI contained five dimensions each consisting of three items. An online survey with university students (n = 1815, 75.1% female, average age: 24.15 years) was administered to test the validity of the Portuguese version of the DHLI. Data were analysed using exploratory and confirmatory factor analysis. Pearson correlations were also studied. Results: Two items revealed symmetry and kurtosis problems. We chose to eliminate them from the analysis. Different exploratory factor analysis attempts were made, obtaining two possible models to be tested in the confirmatory factor analysis: a three‐factor model and a four‐factor model. A four‐factor structure of the instrument (information searching, adding self‐generated content, evaluating reliability, determining relevance) was supported by confirmatory factor analysis and had good internal consistency. Conclusions: The Portuguese version of the Digital Health Literacy Instrument met adequate psychometric criteria. Therefore, it can be confidently used in Portuguese students' assessment of digital health literacy. Representative studies are needed to shed light on different target groups and their COVID‐19–related DHLI.